Efficacy of Atypical-Atypical and Atypical-Typical Antipsychotic in Indonesia Psychotic Mental Disorder Patients - Mexsi Mutia Rissa (CV. Syntax Corporation Indonesia, 2024)
It is approximately 7% of Indonesian people undergo psychotic mental disorder or schizophrenia. Special Region of Yogyakarta in Indonesian is on the second rank as the area whose high number of schizophrenia; for about 10 occurrences per 1000 citizens and 80% of patients treated at psychiatric hospital are caused by schizophrenia. A response of a medication therapy can be measured through doctor diagnosis based on the measurement parameter such as The Positive and Negative Syndrome Scale-Excited Component (PANSS-EC) and Global Assessment of Functioning (GAF). Those two parameters are important variables that will be shown objectively by the assessment results. This research aimed to find out the different value of PANSS-EC and GAF, before and after the therapy of atypical-typical and atypical-typical on the schizophrenia patients at Psychiatric Hospital of Grhasia Yogyakarta. The research design here is Prospective Cohort. The criteria of inclusive patient was adults (18-65 years old), being hospitalized, undergoing atypical-atypical and atypical-typical therapy, and possessing complete medical record. The research data were gained from the medical records which then analyzed using univariate test to illustrate the patient distribution. Bivariate test was conducted to compare and correlate the value of PANSS-EC and GAF. The number of samples were 32 patients which were divided into 2 groups; atypical-atypical (n=16) and atypical-typical (n=16). The results showed that the value of PANSS-EC after therapy in both groups experienced a significant decrease (p=0.001). However, there was no significant difference between the two groups of patients with psychotic mental disorders or schizophrenia in a mental hospital and there reseach no significant difference in effectiveness between doses and frecuency of antipsychotic therapy regimens in schizophrenic patients with a significant value of p>0.05